Determinants of Secondary Job Ownership Among Unskilled Workers in Bali Province - Komang Dea Ayu Maheswari; Ida Ayu Gde Dyastari Saskara; Luh Gede Meydianawathi; I Gusti Agung Ayu Apsari Anandari (International Journal of Management Research and Economics, 2025)
In this modern era, it turns out that there are still many Indonesian workers who are still predominantly low skilled or low skilled. This is what causes many workers to be found in the formal sector with guaranteed income but who have side jobs outside of their main job. There are various reasons that motivate workers to have a side job, such as increasing family income, filling free time, or pursuing a hobby. The aim of this research is to determine the influence of unskilled workers on the decision to have additional work (secondary jobs) in Bali Province, both simultaneously and partially, as well as to determine the influence of control variables on the dependent variable. The approach used in this research is a quantitative approach in associative form. The research locations were carried out in 9 (nine) Regencies/Cities of Bali Province using raw data released by the National Labor Force Survey (SAKERNAS) August 2023. The analysis technique used was the logistic regression analysis technique. The results of the analysis show that the independent variables and control variables simultaneously influence the dependent variable. The variables Education, Family Members and Age have a partially negative effect on the decision to have an additional job (secondary job) in Bali Province. The variables Type of Job, Certified Training, Working Hours, Marital Status, Gender, and Generation (X, Y and Z) have a partial positive effect on the decision to have an additional job (secondary job) in Bali Province. Meanwhile, unskilled workers and income do not influence the decision to have an additional job (secondary job) in Bali Province.